KETIMPANGAN GENDER DAN PERPAJAKAN DI INDONESIA - Alamanda, Alamanda (JURNAL INFO ARTHA, 2023)
This paper aims to analyze the effect of gender inequality on individual income tax revenue in Indonesia. Using panel data analysis of 34 provinces from 2015 to 2020, this paper finds that gender inequality has a negative significant impact on individual income tax revenue. Empirical evidence, both Pooled OLS and Random Effect Model, suggest that a one-point decrease in Gender Inequality Index will increase individual income tax revenue by 0.83 percent on average. Moreover, the paper finds that the effect of inequality gender on individual income tax revenue is higher in Sumatera, Kalimantan, Sulawesi, Papua, and Nusa Tenggara than in Java and Bali islands. Based on this finding, this paper tries to provide a set of gender-responsive tax policies to improve gender equality and tax revenue in the future.